Referenciais freireanos na prática pedagógica: um estudo em uma escola pública do Município de Itajubá-MG - Sá, Isaura F. Vassalo de (2012)
This work aims to analyze the Freirean categories. dialogue and participation in a practice in a state school at the city of Itajubá - MG. We selected a school where the dialogic and participatory practice was already recognized by the community and government bodies of the Department of Education, in order to identifyand analyze how the school makes and remakes it is practices, uided by relevant categories of thought of Paulo Freire. The research is a qualitative approach to methodological choice. Data collection included the following: analysis of school documents, interviews and questionnaires to teachers, students, employees in the educational and administrative situations and observation of planning and development of teaching practice school investigated. Data analysis is supported in the frame Freire, with emphasis on dialogue and participation categories. The collected data indicate the presence of dialogue and participation, in Freirean perspective in the pursuit of collective construction of a democratic school, competent and cheerful. It is clear, however, that although present, the studied categories: dialogue and participation require a permanent job training of teachers for the understanding of these categories, by themselves, be more